1989
DOI: 10.1002/cm.970120406
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the β‐subunit to spectrin structure and function

Abstract: The three avian spectrins that have been characterized consist of a common alpha-subunit (240 kD) paired with an isoform-specific beta-subunit from either erythrocyte (220 or 230 kD), brain (235 kD), or intestinal brush border (260 kD). Analysis of avian spectrins, with their naturally occurring "subunit replacement" has proved useful in assessing the relative contribution of each subunit to spectrin function. In this study we have completed a survey of avian spectrin binding properties and present morphometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 58 publications
1
22
1
Order By: Relevance
“…Thus the three-step in vitro cascade depicted here may have implications for our understanding of the control of receptor organization and plasma membrane dynamics in vivo. It has been hypothesized that the fodrin-based cortical cytoskeleton might serve as an organizer of topographic membrane domains, a targeting mechanism for vesicles containing membrane proteins, a stabilizer of the plasma membrane, and as a barrier to unregulated vesicle traffic (1). These processes probably involve transient changes in the plasticity of the cortical cytoskeleton and its linkage to membrane receptors and microfilaments (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the three-step in vitro cascade depicted here may have implications for our understanding of the control of receptor organization and plasma membrane dynamics in vivo. It has been hypothesized that the fodrin-based cortical cytoskeleton might serve as an organizer of topographic membrane domains, a targeting mechanism for vesicles containing membrane proteins, a stabilizer of the plasma membrane, and as a barrier to unregulated vesicle traffic (1). These processes probably involve transient changes in the plasticity of the cortical cytoskeleton and its linkage to membrane receptors and microfilaments (28).…”
Section: Methodsmentioning
confidence: 99%
“…Fodrin is a ubiquitous cytoskeletal protein involved with organizing receptor domains and possibly the control of vesicle traffic at the plasma membrane (1). Central to its action is its ability to link integral membrane proteins to cortical actin filaments.…”
mentioning
confidence: 99%
“…βHeavy-spectrin isoforms do not bind to ankyrin (Coleman et al, 1989;Lee et al, 1997;Thomas et al, 1997), indicating that other interactions must mediate its recruitment to the membrane. We have previously reported that mutations in the karst locus, which produce truncated βH isoforms lacking the C-terminus and tetramerization site, do not detectably accumulate at the plasma membrane in epithelial cells (Medina et al, 2002;Zarnescu, 2000) (Fig.…”
mentioning
confidence: 99%
“…For example, although the known a subunits are very similar to each other in molecular mass (-280 kDa), the molecular mass of known 13-spectrins range from 246 kDa to 430 kDa (1,2). In addition, diversity in the /8 subunits is thought to account for most of the distinctive structural and functional attributes of different spectrin isoforms (3,4).…”
mentioning
confidence: 99%